Congenital dyserythropoietic anaemia type II (HEMPAS): a family study. Issue 12 (December 1980) - McCann, S R; Firth, R; Murray, N; Temperley, I J
Abstract : A family having two affected siblings with congenital dyserythropoietic anaemia type II (HEMPAS) is described. The proband was diagnosed after referral for investigation of haemolytic anaemia. Clinical evaluation and in vivo red cell (RBC) survival and the sequestration studies in the proband indicated that the anaemia was due to a combination of ineffective erythropoiesis and premature destruction of RBCs in the spleen. Scanning electron microscopic examination of peripheral RBCs was undertaken and is reported. The polypeptide composition of RBC membranes was also examined using polyacrylamide gel electrophoresis after solubilisation in sodium dodecyl sulphate. These results are also reported.